Control of Changes in the Function of Residential Houses to Business Buildings in Urban Areas - Ernawati, Ernawati; Susetya Herawati; Budi Supriyatno (SEAN Institute, 2021)
The limitation of land and its expensive cost in urban areas led to the invasion of commercial functions into the settlement area. The transformation of housing into business buildings is due to population growth within the city and increased activity, where land remains constant so that it cannot accommodate the needs of urban communities. Among these phenomena is the doubled use of housing – for housing and business – to secure additional income/economic boost for the family. As a result, space layout patterns are uncontrolled, and the functions set in the space plan are not achieved. This, in turn, has interfered with the activity and comfort of the environmental functions of the Hunian as a decent Huni. This research aims to produce a formula for the control of the movement of housing functions into business buildings, where the change of the housing function to business building has taken place since 2008 when Law No. 51 of 2008 on the Establishment of the City of Southern Tangerang as an Autonomous District. The method used is a qualitative and quantitative approach with overlay analysis, descriptive analysis, policy analysis and monitoring and control analysis relevant to the intensity of space utilization. (karakteristik nilai tanah, kelengkapan utilitas, aksesibilitas tanah, karakteristik pribadi pemilik tanah, aturan penggunaan tanah, inisiatif bangunan komersial). The uncontrolled change in the function of the residential house into the building of the business building caused a lack of spatial arrangement along the main street corridors in the housing area as a residential place in the urban area caused by the presence of the factors.